Chapter L'eredità teatrale e artistica di Savva Mamontov: un ponte tra Oriente e Occidente - GAVRILOVICH, DONATELLA (Biblioteca di Studi Slavistici, 2017)
The present issue focuses on Savva Mamontov as main creator of a theatrical-synaesthetic experimentation in Russia, based on the research of a common Slavic and pre-Helenic civilizations root to create a universal artistic language. So the paper explores Sciamanism and Shiite mother goddess cult to identify the conjunction points between these ancient cults and the rediscovery of the artist's gesture sacredness both in Mamontov's conception both in the painters' artworks of his circle.